2015
DOI: 10.1002/2014wr016085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring storage and runoff generation processes for urban flooding through a physically based watershed model

Abstract: A physically based model of the 14 km 2 Dead Run watershed in Baltimore County, MD was created to test the impacts of detention basin storage and soil storage on the hydrologic response of a small urban watershed during flood events. The Dead Run model was created using the Gridded Surface Subsurface Hydrologic Analysis (GSSHA) algorithms and validated using U.S. Geological Survey stream gaging observations for the Dead Run watershed and 5 subbasins over the largest 21 warm season flood events during [2008][20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…Booth and Jackson () found that detention basins in the Pacific Northwest, United States, were able to reduce peak flows, but that flow volume and duration were not able to be controlled by detention basins. Near Baltimore, Maryland, United States, Smith et al () modelled the detention basin network of the Dead Run watershed and found that detention basins reduced peak flows by a median of 11%, whereas an earlier study of stream gage data suggested that the basins may have lowered water yield by increasing evaporation (Nelson, Smith, & Miller, ). However, other modelling studies have found that detention basins may increase peak flows where changes in flow timing leads to synchronization from different parts of the watershed (Emerson et al, ; McCuen, , ).…”
Section: Results Of Existing Studiesmentioning
confidence: 99%
“…Booth and Jackson () found that detention basins in the Pacific Northwest, United States, were able to reduce peak flows, but that flow volume and duration were not able to be controlled by detention basins. Near Baltimore, Maryland, United States, Smith et al () modelled the detention basin network of the Dead Run watershed and found that detention basins reduced peak flows by a median of 11%, whereas an earlier study of stream gage data suggested that the basins may have lowered water yield by increasing evaporation (Nelson, Smith, & Miller, ). However, other modelling studies have found that detention basins may increase peak flows where changes in flow timing leads to synchronization from different parts of the watershed (Emerson et al, ; McCuen, , ).…”
Section: Results Of Existing Studiesmentioning
confidence: 99%
“…Smith et al (2015) studied the influence of this phenomenon on peak runoff flow by applying 21 storm events on a physically based, minimally calibrated model of the dead run urban area (USA) with and without the compacted soil layer. Results showed that the compacted soil layer reduced infiltration by 70-90 % and increased peak discharge by 6.8 %.…”
Section: Groundwater Recharge and Subsurface Processes In Urban Areasmentioning
confidence: 99%
“…Results showed a significant increase in peak discharge and runoff volume for drainage density between 0.4 and 0.9 km km −2 , while for values higher than 0.9 km km −2 , effects were negligible. When the storage and transport capacity of a system is not sufficient to prevent flooding, detention basins are effective tools to reduce peak flows, and they can reduce the superficial runoff up to 11 % (Smith et al, 2015).…”
Section: Flow In Sewer Systemsmentioning
confidence: 99%
“…Placement and configuration of imperviousness within a catchment can have a significant influence on downstream response (Mejía and Moglen, ). Locations and configuration of conventional conveyance (Meierdiercks et al ., ; Ogden et al ., ; Tague and Pohl‐Costello, ), infiltration‐based (Easton et al ., ; Gobel et al ., ; Miles and Band, ) and detention‐based (Smith et al ., ) stormwater management infrastructures also influence incremental connectivity in hydrologic response of a catchment under varying event depths.…”
Section: Urban Variable Source Areamentioning
confidence: 99%